Analisis Kemampuan Berpikir Kritis Melalui Model Pembelajaran Problem Based Learning Kelas IV SDN Pandeanlamper 03 Kota Semarang - Lutnatul Jannah; Ikha Listyarini; Aryo Andri Nugroho; Susilo Adi Saputro (Departement of Mathematics Education, 2023)
The independent curriculum's problem-based learning model promotes the development of a skill called critical thinking, which is necessary for learning in the twenty-first century. This study uses a model of problem-based learning to describe the critical thinking abilities of fourth grade students. Descriptive qualitative research is the method employed. 28 fourth-grade students at SDN Pandeanlamper 03 in Semarang City served as the study's participants. Data for the study were gathered from documentation, class teacher interviews, and observations. Data reduction, data presentation, and conclusion-drawing techniques are used when analyzing research data. Observations of critical thinking abilities in class IV students who have adopted the independent learning curriculum. Students engage in discussions and problem-solve while presenting issues connected to the material being taught in order to improve their critical thinking abilities.